Association of pain between elastomeric and the kesling sparators in the orthodontic patients - Khanal, Abhilasha; Bajracharya, Manish; Shrestha, Neesha (Orthodontic Journal of Nepal, 2021)
Introduction: Pain may be experienced during the first 3-4 days of fixed Orthodontic appliance activation. The lesser the pain perceived by a patient, better the treatment outcome and the patient compliance. The post separator placement pain increases as soon as 4 hours and gradually increases over the next 24 hours which is worst at the day 2-4. The Aim of the study is to find out the association of post separator placement pain in our population. Also, the study focuses on the use of dose Paracetamol 500gms, by our patients in case of pain. Materials and Method: Elastomeric separator was placed mesially and distally to the upper right first permanent molar(16) and the kesling separator was placed to the left first permanent molar(26) in 100 orthodontic patients . Patients were given a questionnaire that documented perceived pain, pain on chewing, pain affecting the daily life activities. The patient documented the intake of medication to reduce the pain, if at all. Two different Pain rating scales (PRS) along a line will be used to depict the pain perception. The subjects were asked to circle a spot on the line that they believed best represented the pain they perceived at that time. The evaluation of pain and documentation started on the 4th hour, 24th hrs, 2nd day, 3rd day, 4th day, 5th day, 6th day and the 7th day. Scores 1-3 will be considered as mild pain; 4-6 will be moderate pain and 7-10 is considered to be the severe pain. At every time slot, the pain was documented, there was a spot where the patient has mentioned if he / she used the medication prescribed by the orthodontist. Results: No association of Kesling separators with Pain on chewing , pain perception and pain affecting life at 4th hour, 24th hour, 2nd day, 3rd day, 4th day, 5th day, 6th day, 7th day post separator placement. Association of Medication with the post separator placement pain also is not significant. Significant association of elastomeric separators with pain perception and pain affecting life at 4th hour (p= 0.002 & p=0.005), 24th hour (p= 0.002). Significant Association of Medication with the post separator placement pain also is significant at 4th (p=0.00) and 24th hour (p=0.02) of post separator placement. Conclusion: There is a significant association of elastomeric separators with pain perception and pain affecting life at 4th hour, 24th hour. Significant Association of Medication with the post separator placement pain also is significant at 4th and 24th hour of post separator placement